Pemikiran Neo-Moderisme Nurcholis Madjid - Irma Sari (CV. ULIL ALBAB CORP, 2023)
This article discuss Nurcholis Madjid’s Neo-Moderist Thoughts about Neo-Moderism. This research is library in nature, namely using library materials and other literature as the main data. The results of this research show that there are three thoughts of Nurcholis Madjid regarding Neo-Moderism, Namely: First, according to Nurcholis Madjid, tawhid is the basic principle of Islamic renewal. According to him, all the basics of a comprehensive life journey are contained in the Al-Quran. Second, secularization. This idea is intented to “devaluate” or “demythologize” what is contrary to monotheism. Third, Islam and the Problem of Modernity. Nurcholis Madjid believes that modernization is not an application of secularism or the use of Western cultural values.